2022
DOI: 10.3390/ani12121492
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Semen Collection Affects Ram Sperm Cryoresistance

Abstract: The improvement of frozen-thawed sperm quality has been mostly approached from the view of cryopreservation protocol optimization in terms of cryoprotectant solutions, freezing-thawing rates and antioxidant supplementation, while the impact of sperm collection frequency remains unknown in rams. In this work, a multiparametric study was carried out in cooled and frozen-thawed semen to evaluate sperm quality after different semen collection frequencies during a month: zero sperm collection (0 CW), four sperm col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…CRDR has been considered an ROS marker in ram ( 35 , 50 ), bull ( 38 , 51 ) and stallion sperm ( 44 , 52 54 ). However, contradictory results have been published concerning their correlation with sperm quality in rams ( 42 , 55 , 56 ) and stallions ( 57 , 58 ). These results could suggest that there may be a species-specific effect, which we have decided to study in depth.…”
Section: Discussionmentioning
confidence: 99%
“…CRDR has been considered an ROS marker in ram ( 35 , 50 ), bull ( 38 , 51 ) and stallion sperm ( 44 , 52 54 ). However, contradictory results have been published concerning their correlation with sperm quality in rams ( 42 , 55 , 56 ) and stallions ( 57 , 58 ). These results could suggest that there may be a species-specific effect, which we have decided to study in depth.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our morphometric assessments showed a wide variability prior to, during, and after the mating period. Effects on spermatogenesis can give rise to variations in the size of the spermatozoa and could explain the results observed for sperm head and midpiece size and shape variables that were low after mating; it could be specially related with frequency of collection/ejaculation [ 65 ] and a competition effect between males [ 66 , 67 ]. Moreover, Kondracki et al [ 68 ] reported in bulls that sperm head size increases as the sperm concentration of the ejaculate decreases.…”
Section: Discussionmentioning
confidence: 99%
“…According to Montes-Garrido et al [41], sperm motility and functionality were lower at 6 h post-collection (the time at which vaginal artificial insemination is performed) in the spermatozoa of rams that were overworked. Moreover, the commercial potential of overworked rams is also reduced for frozen-thawed doses, since previous authors have described the lower cryotolerance of spermatozoa produced in a high regime of collection due to a higher oxidative stress through the activity of glutathione peroxidase and superoxide dismutase [51]. Despite all this, it would be interesting to consider the economic impact of specific rams and the need to use them to accelerate genetic improvement.…”
Section: Discussionmentioning
confidence: 99%